Enhancing Students’ Creative Thinking through Inquiry-Based Learning Integrating Mathematical Tools - Nanda Ayu Indarasati; Abadi Abadi; Agung Lukito (SAINTIS Publishing, 2019)
Students were demanded to be a creative problem solver in the career world. A mathematical learning following an inquiry-based learning approach and integrating mathematical tools was developed in this study. Students constructed original solutions about trigonometry ratio by using a clinometer and a meter as mathematical tools in allowing creative thinking. The product was designed through ADDIE methodology and applied to two classes in a Senior High School. A pre-test and post-test design measured cognitive knowledge as creative thinking variable. The result showed that this product with using mathematical tools was feasible and successful in enhancing students’ creative thinking. Inquiry-based learning was developed by involving three main components: providing students with a contextual mathematical problem-solving activity; involving student in an open-ended investigation with using a clinometer and a meter as mathematical tools to promote their creative thinking in creating original solutions; motivating students to build their own knowledge. This inquiry-based learning which had been developed significantly influenced students’ pre-knowledge scores. It could be concluded that creative thinking contributed, too. A recommendation for mathematics teachers in teaching mathematics was to involve students in problem-solving activity that facilitated them to conduct open-ended investigation whereas they could construct their own knowledge in building an original solution.